INVESTMENT SUPPORT INNOVATIVE INDUSTRIAL ENTERPRISES - Gavatiuk, Liudmyla (Journal Association 1901 "SEPIKE", 2016)
European integration as a key foreign policy priority of Ukraine determines the need for more careful study paradigm, goals and strategic plans for economic and social development of European society, taking into account the experience, with all its achievements and losses have become target development strategy for Ukraine in the near future. The priorities of socio-economic development of European society in the near future, as defined in the EU strategy "Europe-2020" aimed at intelligent growth, based on investments in education, research and innovation; sustainable growth as the economy based on sustainability, efficient and economical use of natural resources; inclusive growth aims to reduce poverty, ensuring maximum performance of employment; based on the principles of social inclusion, indicate that the most important role in the strategy assigned to social issues, which are considered as factors and aims of economic growth.
Keywords: innovation, potential, investment, investor, innovative strategy, development, measures, profit